Conception on the evaluative practice of the teachers in distance studies (Encuentros, 2020)
The purpose of this research is to unveil the conception on the evaluative practices who have teachers of the National Open University of Venezuela (UNA, in Spanish). It was made a qualitative and ethnographic research. Observation and interview techniques were used to collect information. The key informants were content specialists, evaluators and advisors of the UNA. The research findings were that the evaluative practices of teachers and the vision they have about them are rooted in the technical conception of teaching and in the second generation of evaluation, because this is how the educational and evaluative model of UNA is thought.KEYWORDS: Evaluation practice, Evaluation of learning, Teaching conception.